Changes of heavy metal concentrations in Shitalakhya river water of Bangladesh with seasons - Kabir, Md. Humayun; Islam, Md. Sirajul; Tusher, Tanmoy Roy; Hoq, Md. Enamul; Mamun, Shamim Al (Universitas Pendidikan Indonesia, 2020)
Heavy metal concentrations in water and fish of the Shitalakhya river was measured to find out the suitability of its water for drinking and irrigation purposes. The concentrations of Pb, Cu, Cr, Zn, Cd and Hg in water were 0.0065; 0.0240; 0.0069; 0.8170; 0.0044; and 0.0057 mg/L, respectively in pre-monsoon, 0.0029; 0.0151; 0.0019; 0.4270; 0.0015; and 0.0020 mg/L, respectively in monsoon, and 0.0040; 0.0212; 0.0039; 0.6520; 0.0029; and 0.0031 mg/L, respectively in post-monsoon season. The heavy metal concentrations were found higher in pre-monsoon followed by post-monsoon and monsoon. The results also depicted that over the three seasons heavy metal pollution index and heavy metal evaluation index for all metals were lower than the critical pollution index value and low heavy metal contamination, respectively, and the degree of contamination in pre-monsoon season stated medium level pollution, followed by post-monsoon and monsoon season. The concentrations of Pb, Cu, and Cr in fish were found less than the lower detection limit, while the Zn were found 25.42; 18.30; and 29.34 mg/kg during the pre-monsoon, monsoon and post-monsoon, respectively. The study concluded that the Shitalakhya river water was not safe for the aquatic environment, especially for aquatic biota.